PROMOTING PRAGMATICS KNOWLEDGE TO STUDENTS OF ENGLISH EDUCATIONANDENGLISHLITERATURESTUDYPROGRAMTOFACEAN UNDERGRADUATE THESIS EXAMINATION - - Margana (Universitas Muhammadiyah Surakarta, 2014)
This paper deals with promoting knowledge of pragmatics which focuses on the knowledge of the illocutionary acts and conversational implicatures to students of English education and English literature study program. It is aimed at describing types of illocutionary acts, illocutionary forces, and conversational implicatures in the context of undergraduate thesis examination. Such types of knowledge of the illocutionary and implicatures are great importance for those students as it confers a clear description of use of speech acts in the context of the undergraduate thesis examination. In reference to these issues, students of English education and English literature study program should be familiar with five types of illocutionary acts which include (1) representatives, (2) directives, (3) commissive, (4) expressive, and (5) declarative. Besides, they are encouraged to clearly understand the nature of the illocutionary forces of each illocutionary act which guides them to make sense of the intentions as performed in the illocutionary act. Added to this, knowledge of conversational implicatures used in undergraduate thesis examination should be clearly understood. The types of implicatures include generalized conversational implicatures and particularized conversational implicatures. This suggests that students who are going to defend their undergraduate thesis draft should be well-prepared and familiar with the types of illocutionary forces and conversational implicatures in order that mis-conception and mis-interpretation of speech acts employed by examiners can be minimized.